Effectiveness of opiate substitution treatment in reducing HIV risk behaviors among African, Caribbean, and Black people: a systematic review. Issue 8 (12th August 2021) - Nguemo Djiometio, Joseph B.; Buzuayew, Asfaw; Mohamud, Hodan; Njoroge, Irene; Kahan, Meldon; Nelson, LaRon E.
ABSTRACT: Objective: The objective of this systematic review is to identify, appraise, and synthesize the best available evidence on the effectiveness of opioid substitution treatment in reducing HIV risk behavior among African, Caribbean, and Black people. Introduction: Substance use plays an important role in HIV transmission among Black people by increasing risky sexual behavior and the risk of HIV acquisition. Opioid substitution treatment, such as methadone maintenance treatment and buprenorphine therapy, has been found to be an effective measure to minimize HIV transmission attributable to opioid addiction. Inclusion criteria: The current review considered studies that included African, Caribbean, and Black adult patients, aged 18 years or over, who have used methadone maintenance treatment or buprenorphine therapies as part of the intervention for opioid use disorders and have been evaluated for sex- and drug-related HIV risk behaviors. This review considered studies that have evaluated the impact of methadone maintenance treatment or buprenorphine therapy on sex- and drug-related HIV risk behaviors. Methods: Multiple databases were searched, including Embase, MEDLINE, PsycINFO, Cochrane Central Register of Controlled Trials, OpenGrey, Grey Matters, New York Academy of Medicine Grey Literature Report, ClinicalTrials.gov, and WHO International Clinical Trials Registry Platform. Two reviewers independently assessed all titles and abstracts, and potentially relevant studies were retrieved in full. Papers selected for retrieval were assessed by two independent reviewers for methodological validity. Data were then extracted from papers. Statistical pooling of quantitative data and meta-analysis was not possible due to heterogeneity of data. Results: Five articles were included in this review: three randomized controlled trials, one cohort study, and one quasi-experimental study. Four studies focused on methadone maintenance treatment and one study discussed the effectiveness of buprenorphine intervention. All studies were from the United States. One study enrolled participants in methadone maintenance treatment for heroin injectors, of which 10% of the sample was HIV positive. These papers included studies that reported a significant reduction in sex-related HIV risk behavior, including having multiple sex partners, frequency of sexual intercourse, condom use, prostitution, and sex trade. Of the five studies, two reported on drug-related HIV risk behaviors, citing a reduction in drug-related HIV risk behaviors. Also, these papers showed unexpected outcomes relating to frequency of sexual intercourse, prostitution, and sex trade. One study reported a significantly higher number of sexual encounters among persons not participating in treatment. One study reported decreasing prostitution and sex trade among individuals receiving methadone maintenance treatment intervention. Conclusion: Methadone maintenance treatment or buprenorphine therapy can be effective in reducing sex- and drug-related HIV risk behaviors among African, Caribbean, and Black people. However, due to the weaknesses in the body of evidence and the quality of evidence, it is not possible to make strong conclusions about these interventions. Rigorous studies are necessary to generate more findings and reinforce the body of literature. Systematic review registration number: PROSPERO CRD42019126954